Anatomical variations in cortical bone surface permeability: Tibia versus femur. (January 2021) - Kumar, Rakesh; Tiwari, Abhishek Kumar; Tripathi, Dharmendra; Main, Russell P.; Kumar, Navin; Sihota, Praveer; Ambwani, Sonu; Sharma, Niti Nipun
Abstract: Cortical bone surfaces (periosteal and endosteal) exhibit differential (re)modelling response to mechanical loading. This poses a serious challenge in establishing an in silico model to predict site-specific new bone formation as a function of mechanical stimulus. In this regard, mechanical loading-induced fluid motion in lacunar-canalicular system (LCS) is assumed osteogenic. Micro-architectural properties, especially permeability regulate canalicular fluid motion within the bone. The knowledge of these properties is required to compute flow distribution. Along the same line, it is possible that cortical surfaces may experience differential fluid distribution due to anatomical variations in microarchitectural properties which may induce distinct new bone response at cortical surfaces. Nevertheless, these properties are not well reported for cortical surfaces in the literature. Accordingly, the present study aims to measure microarchitectural properties especially permeability at different anatomical locations (medial, lateral, anterior, and posterior) of periosteal and endosteal surfaces using nanoindentation. A standard poroelastic optimization technique was used to estimate permeability, shear modulus, and Poisson's ratio. The properties are also compared for two weight-bearing bones i.e. tibia and femur. Endosteal surface was found more permeable as compared to the periosteal surface. Tibial endosteal surface had shown greater permeability values at most of the anatomical locations as compared to femoral endosteal surface. The outcomes may be used to precisely predict site-specific osteogenesis in cortical bone as a function of canalicular flow distribution. This work may ultimately be beneficial in designing the loading parameters to stimulate desired new bone response for the prevention and the cure of bone loss.